Sprouting wings : the true story of James Herman Banning, the first African American pilot to fly across the United States - Jaggar, Louisa; Becker, Shari (Crown Books for Young Readers, 2021)
"James Herman Banning always dreamed of touching the sky. But how could a farm boy from Oklahoma find a plane? And how would he learn to fly it? None of the other pilots looked like him. In a journey that would span 3,300 miles, take twenty-one days, and inspire a nation, James Herman Banning proved that you can't put barriers on dreams." -- Amazon.com.